Need Analysis of English Conversation for Hawkers in Mandalika Special Economic Zone, West Nusa Tenggara - Jumrah Jumrah; Khaerani Saputri Imran (Institut Agama Islam Negeri Palopo, 2024)
The research aimed to investigate the English proficiency level, what English conversation materials are needed, and what obstacles hawkers face in Mandalika Special Economy Zone when communicating with foreign tourists. This study utilizes a qualitative research paradigm with a descriptive approach; this study paints a comprehensive picture of the language abilities of Mandalika's hawkers, the materials of English conversation needed by hawkers, and the hawkers' obstacles when communicating with foreign tourists. Methods of collecting data consist of interviews, documentation, and observation. Some steps to analyze the data collected are data condensation, data display, verification, concluding, and data validity. Findings reveal a diverse spectrum of English proficiency levels among hawkers, ranging in primary and intermediate proficiency levels. Specifically, from 20 hawkers as research subjects, 13 hawkers exhibit a basic level of proficiency, while seven hawkers demonstrate intermediate-level skills. The assessment of English proficiency level is based on three crucial aspects that the hawkers always use namely understanding of English communication, non-verbal communication strategies employed by the hawkers, and vocabulary usage. These materials vary depending on the type of goods hawkers sell, highlighting the importance of tailored language resources. This research found 4 (four) crucial materials or topics to be mastered when communicating with foreign tourists: greetings and welcoming, describing specialties, providing personal/additional information, and discussing prices and payment. Additionally, the research uncovers obstacles faced by hawkers in their communication with foreign tourists. These challenges encompass hawkers' difficulty in explaining products, the low English proficiency of most Hawkers, and also language and vocabulary constraints of hawkers.